Model geometries of random porous materials - Buchele, Felix; Blank, Michael; Pöschel, Thorsten; Müller, Patric (International Journal of Heat and Mass Transfer, 2024)
We describe a method for modeling the geometry of random porous materials. The approach enables the independent selection of crucial parameters, including porosity, pore size distribution, pore shape, and connectivity. Consequently, it can effectively model a wide range of porous systems. Due to the diverse and systematic variation possibilities, the method is suitable for developing and optimizing porous structures. The geometries can be exported as triangular meshes, facilitating their immediate use in numerical simulation and further digital processing. We showcase the method's capabilities by minimizing the foam structure's thermal conductivity through geometry optimization.
CRIS-Team Scopus Importer:2024-08-30
Keywords: Numerical modeling; Numerical simulation; Porous geometry; Porous systems; Topology optimization